ASMARADANA'S POETRY: AN OVERVIEW OF LANGUAGE AESTHETICS, JAVANESE MYTHOLOGY, AND THE VALUE OF CHARACTER EDUCATION - Widijanto, Tjahjono (Ruang Kata, 2021)
Abstract-The word in poetry has a paradoxical position. On the one hand, the word is always burdened to convey meaning or meaning. However, on the other hand, the word actually overturns general understanding through the symbols it bears. This research is analyzing the aesthetics of language which includes various sounds, diction, and poetry symbols; discuss the cultural context in the form of Javanese mythology; and linking it with the values of character education. This study uses a qualitative research paradigm. The research data is a collection of Asmaradana poems. Technical data analysis using technical content analysis. The results showed that the effectiveness of diction, the use of various sounds, and the use of symbols in the form of private symbols and natural symbols. Implicitly GM's poems in Asmaradana try to make an imaging effort about human existence along with various fax of humanity and facts of sociocultural awareness. Asmaradana implicitly also stores the values of character education that can be used as a role model for readers. GM not only puts poetry as a flood of sedimentary contemplation, but he also positions poetry as a medium for educational transfer.